2014
DOI: 10.1039/c4tb01101e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TiO2nanoparticles on the performance of polyphenylsulfone biomaterial for orthopaedic implants

Abstract: Nanocomposites of biocompatible polyphenylsulfone (PPSU) and titanium dioxide (TiO 2 ) nanoparticles have been prepared via ultrasonication and solution casting. Their structure, surface morphology, water uptake, thermal, mechanical, tribological and antibacterial properties have been investigated in detail.FT-IR analysis revealed the existence of strong hydrogen bonding interactions between the sulfone group of PPSU and the hydroxyl moieties of the nanoparticles, which were homogenously dispersed within the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 52 publications
4
67
1
2
Order By: Relevance
“…4(b) and (c). 39 Results show most of the peaks appeared in PPSU could also be found in the PPSU/0.8Cu-BTC (Fig. 4(b), the PPSU shows absorption peaks at 1320 and 1151 cm À1 which can be ascribed to the asymmetrical and symmetrical stretching vibrations of the SO 2 group, respectively.…”
Section: Characterization Of Asymmetric Ppsu and Ppsu/cu-btc Mixed Mamentioning
confidence: 82%
“…4(b) and (c). 39 Results show most of the peaks appeared in PPSU could also be found in the PPSU/0.8Cu-BTC (Fig. 4(b), the PPSU shows absorption peaks at 1320 and 1151 cm À1 which can be ascribed to the asymmetrical and symmetrical stretching vibrations of the SO 2 group, respectively.…”
Section: Characterization Of Asymmetric Ppsu and Ppsu/cu-btc Mixed Mamentioning
confidence: 82%
“…The nanofiller content and state of dispersion are very important factors determining the antimicrobial ability of nanocomposite packaging films. Díez‐Pascual and Díez‐Vicente () reported that the minimum TiO 2 content required for effective microbial growth inhibition was 3.0 wt %. On the other hand, the homogeneous nanoparticle distribution in the nanocomposites was related to the strong microbial inactivation.…”
Section: Resultsmentioning
confidence: 99%
“…This activity towards a multidrug resistant bacterium was observed to be close to the behaviour of similar anodic layers modified with the addition of silver [11]. One mechanism was envisioned as responsible for this unexpected antibacterial activity, that is, the formation of reactive oxygen species due to non-stoichiometry of the oxide film, and particularly to a large content of Ti 3+ species as a result of oxygen vacancies: this, together with other features related to TiO 2 nanoparticles rather than to anodic surfaces, was already proved to be a possible source of antimicrobial effects [20,21].…”
Section: Accepted Manuscriptmentioning
confidence: 99%